APPLICATION OF TRIP GENERATION MODELS FOR URBAN TRANSPORT PLANNING IN A DATA SCARCE DEVELOPING COUNTRY CITY: THE CASE OF DAR ES SALAAM - Bwire, Hannibal (Tanzania Journal of Engineering and Technology, 2017)
With the increase in travel demand and traffic management problems in many developing countries cities, travel demand forecasting models are being employed increasingly to make informed decisions about the operational improvements to the existing transportation system and the design and performance of future transportation systems. The main advantage of using travel demand forecasting models for such purposes is that they are capable of capturing the interactive effects of different components of the system under study. However, for some time now there have been concerns about the application of transport planning models in developing countries. The concerns have been mainly in relation to the variables, coefficients and models borrowed from developed countries. This paper first discusses the characteristics of transport problems in developing cities and provides a review of trip generation modelling approaches. Then, the discussion extends further to cover available data for urban transport planning and trip generation models that have found application in Dar es Salaam, Tanzania. The paper concludes by highlighting how available data sources and trip generation modelling approach can be improved to cope with the dynamic conditions in Dar es Salaam.